Committees for ethics in research involving human subjects - Saad Hossne, William [UNESP]; Vieira, Sonia; Bontempo Duca de Freitas, Corina (My University, 2008)
In Brazil since October 1996 there have been guidelines for research involving human subjects. Now human subjects know when their treatment is part of research. Deceit is no longer tolerated. But is not enough to say we offer an explanation to the potential subject and we offer a choice before he or she is confronted with an informed consent form. As in all professional activity, scientific investigation needs social controls. In Brazil, the ultimate responsibility of an investigation lies on the investigator, but in every institution where research is carried out there is a Committee for Ethics in Research. All Committees are subordinated to the National Commission of Ethics in Research, which is submitted to the Brazilian Institute of Health. During 2005 around 17,000 protocols involving 700,000 human subjects were revised by 475 Committees distributed all over the country. Approximately 7,000 people are now working in these Committees.
Keywords: Brazil; Clinical trial; Practice guidelines; Research ethics committes; Research subjects; bioethics; clinical trial; doctor patient relation; drug industry; ethics; human; human experiment; human relation; informed consent; organization and management; patient right; patient selection; practice guideline; professional standard; public health; research ethics; Bioethical Issues; Clinical Trials as Topic; Drug Industry; Ethics Committees, Research; Ethics, Research; Guidelines as Topic; Human Experimentation; Humans; Informed Consent; National Health Programs; Patient Rights; Patient Selection; Physician-Patient Relations; Researcher-Subject Relations